Analisa Pengaruh Pengumuman Merger Dan Akuisisi Terhadap Abnormal Return Saham Bank Umum Di Bursa Efek Indonesia - Rusnanda, Eliya Wahyu; Pardi, Pardi (STIE Surakarta, 2013)
Free trade business competition is getting tougher . Free trade also have an impact on the national banking industry competition . Free trade has given rise to specialization, efficiency and technology transfer . At this level commercial banks must always develop innovations and business strategies in order to survive and even thrive in a climate of intense competition . The merger is one of the solutions in the banking industry for both the existence and expansion . With mergers and acquisitions are expected to stronger capital structure , the transfer of technology , increasing skills , Human Resources more professional , effective and reach more market share and extensive network . The purpose of the study were: 1 ) To investigate the effect of differences in abnormal returns before and after the announcement of the merger and acquisition of commercial banks as akuisitor ; 2 ) To determine the effect of the level of merger and acquisition announcements stock commercial bank to commercial banks as an abnormal return akuisitor. This study is quantitative . The population in this study is the data publicly traded banking company listed on the Stock Exchange are doing a merger or acquisition . The sample used is the data of the merged banking company or an acquirer who has gone public and announced the companys mergers and acquisitions in the year 2006-2010 with a total sampling technique . The data used in this study is secondary data . Data analysis methods used in the study are : Normality Test methods Liliefors of kolmogrov - Smirnov test hypotheses and paired sample t - test ( if normal data ) or wilxocon signed rank test (if the data is not normal). Results of the study : 1 ) The influence increase in the value of the average abnormal return is received from the investor becomes -0.005500 -0.012471 ; 2 ) Hypothesis test results showed that there was no difference in the average abnormal return is significant before and after the merger announcement indicated above 0.05 to be exact significance value 0.469.